The impact of abandonment and intensification on the biodiversity of agriculturally marginal grasslands – a systematic review - Susanna Hempel; Felix Herzog; Péter Batáry; Erik Öckinger; Eva Knop (Basic and Applied Ecology)
Agriculturally marginal grasslands have been traditionally managed at low intensity for centuries and are among Europe’s key biodiversity hotspots. Because of their low profitability, many of them have been either abandoned or subjected to intensified management in recent decades. Both pathways threaten the high diversity of grassland species that depend on traditional management practices. To counteract the negative effects of abandonment or agricultural intensification on biodiversity, restoration and conservation practices were established. Through a systematic literature review based on 174 European studies, we investigated the impacts of abandonment and intensification on various measures of agriculturally marginal grasslands diversity. Additionally, we extracted information on the positive impacts of conservation – defined here as sustained extensive management practices - and restoration efforts aimed at previously abandoned or intensified grasslands. Abandonment had a high probability (71%) of reducing plant and lichen biodiversity, while it was significantly less likely to decrease the diversity of animals (23%). Intensification negatively affected the diversity of all organism groups to a similar extent (65% probability for plants and lichen, 47% for animals). Conservation efforts were likely to maintain or increase animal biodiversity (probability 79%), but in the studies we analysed, they were not sufficient to preserve the biodiversity of plants and lichen. The restoration of abandoned or intensified grasslands was predicted to enhance plant and lichen diversity (68% probability), while not significantly changing animal diversity. Thus, different organisms groups responded differently to changes in agricultural management, highlighting the need for targeted conservation and restoration strategies. By synthesizing biodiversity responses across taxa and management types, this review contributes to a more integrated and evidence-based understanding of how to maintain and improve the ecological value of agriculturally marginal grasslands.